Dexamethasone and Methylprednisolone Promote Cell Proliferation, Capsule Enlargement, and in vivo Dissemination of C. neoformans - Araújo, Glauber R. de S.; Alves, Vinicius; Martins-de-Souza, Pedro H.; Guimarães, Allan J.; Honorato, Leandro; Nimrichter, Leonardo; Takiya, Christina Maeda; Pontes, Bruno; Frases, Susana (Frontiers in Fungal Biology, 2021)
Cryptococcus neoformans is a fungal pathogen that causes life-threatening infections in immunocompromised individuals, who often have some inflammatory condition and, therefore, end up using glucocorticoids, such as dexamethasone and methylprednisolone. Although the effects of this class of molecules during cryptococcosis have been investigated, their consequences for the biology of C. neoformans is less explored. Here, we studied the effects of dexamethasone and methylprednisolone on the metabolism and on the induction of virulence factors in C. neoformans. Our results showed that both glucocorticoids increased fungal cell proliferation and surface electronegativity but reduced capsule and secreted polysaccharide sizes, as well as capsule compaction, by decreasing the density of polysaccharide fibers. We also tested whether glucocorticoids could affect the fungal virulence in Galleria mellonella and mice. Although the survival rate of Galleria larvae increased, those from mice showed a tendency to decrease, with infected animals dying earlier after glucocorticoid treatments. The pathogenesis of spread of cryptococcosis and the interleukin secretion pattern were also assessed for lungs and brains of infected mice. While increases in the spread of the fungus to lungs were observed after treatment with glucocorticoids, a significant difference in brain was observed only for methylprednisolone, although a trend toward increasing was also observed for dexamethasone. Moreover, increases in both pulmonary and cerebral IL-10 production, reduction of IL-6 production but no changes in IL-4, IL-17, and INF-γ were also observed after glucocorticoid treatments. Finally, histopathological analysis confirmed the increase in number of fungal cells in lung and brain tissues of mice previously subjected to dexamethasone or methylprednisolone treatments. Together, our results provide compelling evidence for the effects of dexamethasone and methylprednisolone on the biology of C. neoformans and may have important implications for future clinical treatments, calling attention to the risks of using these glucocorticoids against cryptococcosis or in immunocompromised individuals.